Skeletal variability in British Columbia coastal populations : a descriptive and comparative assessment of cranial morphology - Cybulski, Jerome S. (Mercury series., 1975)
Sample consisted of 315 adult crania from 18 local groups representing four major divisions: Haida, Kwakiutl, Nootka, and Coast Salish.